A study of Swedish speakers' learning of Chinese noun classifiers - Gao, Helena H. (2015)
Chinese noun classifiers are an obligatory category associated with nouns. Studies have shown that achieving a full understanding and good mastery of Chinese noun classifiers is difficult for both young and adult L2 learners. This study examines the learning strategies used by 30 Swedish adults for a period of two months. Their learning results are compared to 30 bilingual children's production of Chinese noun classifiers. The adult learners exhibit a normal top–down learning fashion, in which they fail to acquire the complex semantic and cognitive meanings embedded in the classifiers. The children, on the other hand, apply cognitive strategies with a bottom–up approach. The adults’ learning of classifiers lags surprisingly far behind their general level of Chinese proficiency. This study can be used as a reference for future studies on the conceptual and cognitive aspects of Chinese language acquisition by speakers whose native languages are not classifier languages.